SOCIAL PSYCHOLOGICAL CHARACTERISTICS IN WOMEN'S PROFESSIONAL ACTIVITY - Nasirova Zilolakhan; Akhmedova Irodakhon Murodjon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
A number of social and psychological factors play an important role in women's professional success. This article examines research on gender equality, personal motivation, and societal stereotypes. Special attention is paid to the state policy and practice of women's professional development in our country.